(untitled) (Cadernos de Sociomuseologia, 2017)
This work is about the relation between museum and communication, concerning to the publicity of proposals, activities and scheduling of the own institution. It deals with journalism, public opinion and the need for the museum to be newsworthy, among so many issues that are scheduled by the media, to be able to position itself in the media. The museum itself is a scheduler that selects the object of memory, art, or any other nature to publicize, highlight, emphasize and bring forward, and is therefore also a mediator. So, this permeabilization of the media by the selection that the museum makes becomes a meta-schedule that confirms the choices made to approach the reality, to value and to stand out in the society. In order to problematize these aspects, we use the Agenda-Setting Theory, the concept of public opinion of Walter Lippman and the understanding that there is a need to publicize the cultural patrimony. As an empirical universe, we selected ten museums located in Salvador, Bahia. Keywords: Museam, Agenda Setting, Journalism, Cultural Patrimony